À DESCOBERTA DOS SINAIS DE PISTA - Beatriz Inês Acciaiuoli Azenha Catalão (2024)
Discovering Clues is the document related to the Final Internship Report, prepared as part of the Professional Internship Course Unit within the 2nd Cycle of studies of the Master's Degree in Physical Education Teaching in Basi and Secondary Education, at the Faculty of Sport of the University of Porto. The Professional Internship marks both the end and the beginning of a journey for a student intern, who is a resident and shared class at a Cooperating School. The Professional Internship last for one academic year and is supported by an Internship Team, consisting of a Cooperating Teacher, a Supervising Teacher and three Student Interns. The document aims to describe, reflect on, analyze and evaluate all the work carried out during the Professional Internship, being divided into five main and distinct themes: personal framework, institutional framework, operational framework, community involvement and research in the teaching context. This report is related to a treasure hunt game that involves discovering clues to prepare a journey with all the necessary tools to reach the end. At the beginning of the Professional Internship, the student intern is faced with various challenges and is asked to choose an issue related to the context of their resident class in order to conduct a study addressing the situation. This research in the teaching context explores the evolution of students' motor performance and skills, organized into groups of different levels, homogeneous and heterogeneous groups, in Physical Education classes.